2019
DOI: 10.1017/s0959774319000453
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Gender Differently: New Approaches to Identity Difference in the Central European Neolithic

Abstract: Gender in the European Neolithic has seen little debate, despite major scholarly interest in identity and social relationships. This article considers how gender operated in the Linearbandkeramik (LBK, c. 5500–5000 cal. bc), the first farming culture of central Europe. A new theoretical approach is developed from the philosophy of Deleuze and Guattari, and the feminist philosopher Braidotti, proposing that how difference and variation are conceived is an important element in how identity is experienced and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Our results stress the importance of addressing gender and sex studies on the basis of the particular contextual characteristics of every community, as has been previously stated [ 24 , 42 ]. Even in the 150-year period represented by this study, gender patterns proved to be dynamic as farming spread westwards, consistent with the presence of variability in cultural patterns.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results stress the importance of addressing gender and sex studies on the basis of the particular contextual characteristics of every community, as has been previously stated [ 24 , 42 ]. Even in the 150-year period represented by this study, gender patterns proved to be dynamic as farming spread westwards, consistent with the presence of variability in cultural patterns.…”
Section: Discussionsupporting
confidence: 81%
“…Even in the 150-year period represented by this study, gender patterns proved to be dynamic as farming spread westwards, consistent with the presence of variability in cultural patterns. Those changes in social and symbolic means of expression include shifts in the human mobility patterns, possibly including exogamy practices, an increased presence of unfurnished inhumations, changes in the frequencies and characteristics of certain items considered as status and gender identity markers ( Spondylus ornaments, polished adzes and arrowheads) [ 34 , 42 , 43 , 62 , 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…The grave goods assemblages signalled that gender differences were recognised in the material cultures of these communities, reaching a consensus by which biologically female-sexed skeletons could receive a wider and less sex-determined range of grave goods than their male-sexed counterparts, who were more frequently buried with identity markers, such as polished and bevelled artefacts (hereinafter: "PBAs"), arrows, bone/antler items and fire lighting sets (Van de Velde 1979, Jeunesse 1997, Hedges et al 2013, Nordholz 2015, Augereau 2018, Ib 2019, Müller-Scheeßel 2019. A recent study has concluded that there was diversity and fluidity in female identities, while male identities had more limited possibilities and were subject to more social constraints (Bickle 2019). "…”
Section: Non-english Literature and Other Additional References *mentioning
confidence: 99%
“…A more widely socially fluid setting of LBK communities is to be expected (Furholt 2018). Different relations between local and non-local individuals have been found using strontium isotope analyses (for a summary, Bickle & Whittle 2013), and while patrilocal marriage patterns are often been postulated (Bentley et al 2012; Brandt et al 2014; Pavúk 1972), a wider spectrum of factors influencing mobility patterns is to be expected (Bickle 2019; Bickle & Whittle 2013; Gomart et al 2015; Hofmann 2016). This might include long-distance relocation of individuals, as indicated by the Bükk pottery referred to earlier.…”
Section: The Special Significance Of the Enclosurementioning
confidence: 99%